Pendaftaran Pendirian Badan Usaha Secara Elektronik Melalui Sistem Administrasi Badan Usaha - Ivone Tara Chensita; Raden Murjiyanto (Jurnal Hukum IUS QUIA IUSTUM, 2021)
The purpose of this study intends to identify, first, the legal certainty of granting integrated licensing through Online Single Submission (OSS), in connection with the registration of business entities electronically (online) through the Business Entity Administration System (SABU) at the Director General of AHU of the Ministry of Law and Human Rights. Second, steps that must be taken for companies that have existed before the enactment of company registration through SABU. Third, steps that must be taken in the event of a change related to company data that has been registered through SABU. The research method uses the normative-empirical method. The results of the study concluded that, first, by registering business entities electronically (online), it provides more legal certainty in the services of providing integrated business licensing through OSS. Second, in this case the granting of business licenses in accordance with the business fields that have been inputted and registered in the SABU system and integrated with the system in the OSS, will issue a Business Identification Number (NIB). Third, there must be an amendment to the articles of association, especially in terms of changes regarding the objectives and activities of the business sector, changes must be made by adjusting the list of business fields listed in the 2017 Indonesian Standard Business Field Classification (KBLI). Subsequently registered with the Ministry of Law and Human Rights (on line) via SABU, and a Certificate of Registration for Changing Company Data will be issued.